Dental school tracks related to the retention of dentists in Thai government service: a cross-sectional survey - Philaiporn Vivatbutsiri; Thanachok Iempook; Sakda Wonghinkong; Sunisa Sopa; Palinee Detsomboonrat (BMC, 2020)
Abstract Background The shortage of dentists working in rural hospitals is an important public health problem resulting from dentist distribution inequity. The Ministry of Public Health of Thailand (MoPH) has implemented a policy of recruiting students with a rural background to be dental students and return home after graduating. This study aims to examine the relationship between admission tracks during the academic years 2005-2011 on retaining dentists in Thai government service and identify the factors associated with retention and resignation. Methods A cross-sectional survey was conducted using an online questionnaire from 287 dentists who graduated from Chulalongkorn University (CU) between 2010 and 2016. Follow-up data consisted of the admission track, number of years spent in Thai government service, and factors that influenced their decision to stay or resign from Thai government service. Chi-squared analysis was used to analyze the data. Results The overall retention rate in Thai government service was 58.2%. Dentists in the rural track had a significantly higher retention rate than the normal track (p = 0.023). Female dentists who were married and graduated less than 3 years had a significantly higher resignation rate than others (p < 0.05). The main reasons for retention were "security in the profession," "high chance to pursue specialty training in the future," and "close proximity to hometown." Dentists from the CU rural admission tracks chose "close proximity to hometown" as the top reason, while others selected "security in the profession." The main reasons influencing resignation were "workplace far away from hometown" and "getting specialty training." Conclusions These results indicate that dentists in the rural track had a significantly higher retention rate than the normal track. The most important factor influencing both retention and resignation was workplace location, where being near to their hometown improved the retention rate of rural dentists. Therefore, the MoPH should increase student admission into the rural track to resolve the inequity in dentist distribution.